Plasticidade transgeracional em sementes e plântulas de girassol submetidas ao cádmio e manganês - Bernardes, Mateus Moreira (2021)
High anthropogenic activity can elevate the levels of trace elements in an environment. Once absorbed by plants, these elements, such as cadmium, can be translocated and bioaccumulated in different organs and tissues, including seeds. The stages of germination and seedling establishment are highly sensitive points in plant development and can be impacted by external environmental conditions. However, plants can transmit information that ensure better acclimation of their offspring when they face conditions similar to those experienced by the parental generation, through a mechanism called transgenerational plasticity. In this work, the objective was to understand if seeds from four different origins have some mechanism that allows them a better acclimatization in adverse environments similar to those in which the mother plant that generated such seeds was grown, monitoring the stage of germination and establishment of seedlings. The experiment was performed in an entirely randomized factorial scheme with 4 seed origins (Control, 0Cd0Mn, 5Cd and 5d400Mn) and 3 conditions (Control, 5Cd and 5Cd400Mn) with 4 repetitions each and divided into 2 stages. In the first stage, seeds were characterized as to their germination and imbibition curve and biochemical analyses were performed as to the content of H2O2, MDA, soluble and reducing sugars, proteins, amino acids, proline, besides the activity of SOD, CAT and APX in seeds collected 8 and 24 hours after the beginning of imbibition. In the second stage, the seeds were grown in soil for a period of 25 days followed by collection for the above biochemical analyses, in addition to cadmium and manganese quantification, chlorophyll a fluorescence and biomass. In general, it was possible to evidence the activity of SOD and APX mainly as possible indicators of transgenerational plasticity, besides verifying the influence of the origin of the seeds in the stages of germination and establishment. For seeds, the origin of the material promoted delays in soaking and germination, especially in seeds '5Cd400Mn' in relation to the others. In plants, the effects of the parent plant although little evidenced, were less preponderant than the cultivation condition. However, plants of '5Cd' and '5Cd400Mn' origin showed differences in photochemical capacity relative to the others in the presence of cadmium.